1985
DOI: 10.1007/bf00237851
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between orientation tuning and spatial frequency in neurones of cat area 17

Abstract: The orientation bandwidth was measured at different spatial frequencies for simple and complex cells. With increasing spatial frequency, the orientation tuning of simple cells became progressively narrower. This tendency was much less marked in complex cells. The results are interpreted in support of geniculate cells with orthogonal orientation biases providing the excitatory and inhibitory inputs to a simple cell.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 20 publications
6
24
0
Order By: Relevance
“…We further found that there was a weak but significant correlation between the OSI and the preferred SF for V1 neurons in all mice groups except WT mice at 8 weeks (r = 0.27, P = 0.002 for 8-week Tg1 mice; r = 0.12, P = 0.17 for 8-week WT mice; r = 0.42, P = 9.8 × 10 −5 for 14-week Tg1 mice; r = 0.29, P = 0.004 for 14-week WT mice, Supplementary Fig. S6), consistent with previous reports that orientation tuning is sharper at higher SF 19, 20 and suggesting that higher OSI for Tg1 mice may be due to higher SF preference of the neurons.…”
Section: Resultssupporting
confidence: 90%
“…We further found that there was a weak but significant correlation between the OSI and the preferred SF for V1 neurons in all mice groups except WT mice at 8 weeks (r = 0.27, P = 0.002 for 8-week Tg1 mice; r = 0.12, P = 0.17 for 8-week WT mice; r = 0.42, P = 9.8 × 10 −5 for 14-week Tg1 mice; r = 0.29, P = 0.004 for 14-week WT mice, Supplementary Fig. S6), consistent with previous reports that orientation tuning is sharper at higher SF 19, 20 and suggesting that higher OSI for Tg1 mice may be due to higher SF preference of the neurons.…”
Section: Resultssupporting
confidence: 90%
“…However, this conflict remains unresolved in the experimental literature. Some studies report a lack of separability (24,25), whereas others support separability (26).…”
Section: Discussionmentioning
confidence: 99%
“…One could also compare the degree of cortical sharpening of feedforward tuning with the degree of orientation plasticity in the same V1 cells and see whether they are positively correlated as predicted by our study. A related observation is that orientation tuning width in at least some simple cells changes with the spatial frequency of a stimulus (Vidyasagar & Siguenza, 1985). This observation is better explained by a feedforward model because in a recurrent model, the tuning width is largely determined by intracortical interactions and is not very sensitive to stimulus spatial frequency (Ferster & Miller, 2000; Teich & Qian, 2006).…”
Section: Discussionmentioning
confidence: 99%